Feedback and attitude change the effects of the type of feedback on attitude toward mathematics. - Nismal, Hazel B., Tan, Divine Antoniette L. (College of Arts and Sciences, University of the Philippines Visayas, 1998)
In this study, researchers suggested that giving feedback of the test result would affect students' attitude toward Mathematics. 80 UPV students from the College of Arts and Sciences served as participants in this study. Initial attitude toward Mathematics was determined through pretest measure. Posttest followed right after the different types of feedback were given to the experimental groups. Results showed that there was no significant difference in attitudes of students toward Mathematics before and after feedback, neither there was a difference in attitudes among feedback groups. Interaction among feedback groups before and after feedback, however, yielded a significant difference. It was found that students who were given any feedback of their Math scores hardly changed and their attitudes toward Mathematics. Giving a positive Elaborative Feedback and Knowledge of True Score of the Math performance was proven not to be effective in changing the attitude toward Mathematics. The idea that feedback leads to attitude change only holds true when an extremely negative feedback is presented since those belonged to Negative Elaborative Feedback group changed their attitude from positive to negative. Generally, the findings reflect that feedback is a weak factor to be considered in changing attitude.
Research Experiment (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Mathematics -- Attitude; Students -- Mathematics